Artificial vision: principles and prospects. Issue 1 (February 2017) - Gilhooley, Michael J.; Acheson, James
Abstract : Purpose of review: The aim of this article is to give an overview of the strategies and technologies currently under development to return vision to blind patients and will answer the question: What options exist for artificial vision in patients blind from retinal disease; how close are these to clinical practice? Recent findings: Retinal approaches will be the focus of this review as they are most advanced in terms not only of development, but entry into the imagination of the general public; they are technologies patients ask about, but may be less familiar to practicing neurologists. The prerequisites for retinal survivor cell stimulation are discussed, followed by consideration of the state of the art of four promising methods making use of this principle: electronic prostheses, stem cells, gene therapy and the developing field of ophthalmic optogenetics. Summary: Human applications of artificial vision by survivor cell stimulation are certainly with us in the research clinic and very close to commercialization and general use. This, together with their place in the public consciousness, makes the overview provided by this review particularly helpful to practicing neurologists.